2022
DOI: 10.1186/s12889-022-12595-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with lipid-lowering medications use for primary and secondary prevention of cardiovascular diseases among Malaysians: the REDISCOVER study

Abstract: Background Lipid-lowering medications (LLM) are commonly used for secondary prevention, as well as for primary prevention among patients with high global cardiovascular risk and with diabetes. This study aimed to determine the prevalence of LLM use among high-risk individuals [participants with diabetes, high Framingham general cardiovascular (FRS-CVD) score, existing cardiovascular disease (CVD)] and the factors associated with it. Methods This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…This study discovered that among the VHR participants, about 75.8% were not on LLT. Another local study by Baharudin et al reported a comparable finding where 74.2% of those with existing CVD were also not using any LLT [ 30 ]. In addition, in the present study, the majority of participants on LLT did not achieve LDL-C target levels for their respective risk categories, at the time of evaluation.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This study discovered that among the VHR participants, about 75.8% were not on LLT. Another local study by Baharudin et al reported a comparable finding where 74.2% of those with existing CVD were also not using any LLT [ 30 ]. In addition, in the present study, the majority of participants on LLT did not achieve LDL-C target levels for their respective risk categories, at the time of evaluation.…”
Section: Discussionmentioning
confidence: 89%
“…Baharudin et al highlighted the need for the LLT to be prescribed appropriately based on the patient’s clinical condition. With the proper prescription of LLT, those medically eligible subjects with socio-demographic disadvantages will have equal access to LLT, particularly for common LLT, such as statins, which are free to all Malaysian attending government healthcare facilities [ 30 ]. Furthermore, the poor achievement of the therapeutic LDL-C target from this study, particularly among those in the HR and VHR categories, emphasised an urgent need to improve the awareness of the general public and healthcare providers on the importance of early detection and efficient treatment of dyslipidaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, through MyHEBAT, the participants were informed of their health status which made them aware of whether they have CVD risk or were at the borderline of having the risk. This is essential, as several studies have reported that Malaysians have poor awareness about their risks, diseases, treatment and medication, which could lead to poor control of their CVD risk factors [ 5 , 60 , 61 , 79 , 80 ]. Overall, evidence from the MyHEBAT study will bridge the gaps in the literature and guide academics, policy makers and the industry in their collaborative efforts to battle CVD risk, morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The study duration is 25 years, and data collection is repeated every three years. The methodology for the REDISCOVER Study has been published elsewhere [ 23 , 24 , 25 , 26 ], whereby specific methods were highlighted as relevant to the sub topics. In previous publications, the number of baseline data was different, as the baseline data collection was still ongoing.…”
Section: Methodsmentioning
confidence: 99%